PENGARUH SELF REGULATED LEARNING TERHADAP PRODUKTIVITAS PENDIDIKAN PELAJARAN EKONOMI XI-F SMAN 1 KARTASURA DIMODERASI FASILITAS BELAJAR - Pariduri, Fatmawati; Sudarno (Edunomic : Jurnal Ilmiah Pendidikan Ekonomi Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This research aims to find out how much influence of self regulated learning of educational productivity in Economics subjects for XI-F students at SMAN 1 Kartasura and find out how much influence of self regulated learning of educational productivity in Economics subjects for XI-F students at SMAN 1 Kartasura when moderated by learning facilities. The population 180 students from XI-F SMAN 1 Kartasura. The sample used was determined using SLOVIN formula, resulting 125 students. This research is a descriptive quantitative. The sampling techinique employed was proportionate stratified random sampling, with data obtained questionnaire. Data collection tool uses a questionnaire. Validity was evaluated using Bivariate Correlation, specifically the Pearson Product Moment Correlation Coeffiecient. Reliability was assessed using Cronbach’s Alpha. Data analysis technique used were classical assumption test and hypothesis test. The classical assumption test included the normality test, linearity test, multicollinearity test, and heterokedasticity test. Hypothesis test was conducted using t test, simple linear regression, and moderated regression analysis. The result of this study indicates that there is influence of self regulated learning of educational productivity in Economics subjects for XI-F students at SMAN 1 Kartasura and there is no influence of self regulated learning of educational productivity in Economics subjects for XI-F SMAN 1 Kartasura when moderated by learning facilities. This shows that the factors from intern and extern have an important role in the success of students in educational productivity. Keywords: educational productivity, learning facilities, self regulated learning